2014
DOI: 10.1093/pubmed/fdu024
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing coroners' verdicts: an analysis of verdicts given in 12 coroners’ districts to researcher-defined suicides in England in 2005

Abstract: Coroners vary considerably in the verdicts they give to individuals who probably died by suicide. This may compromise the usefulness of suicide statistics for assessing area differences in rates for public health surveillance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 14 publications
2
26
1
Order By: Relevance
“…Possible underreporting of suicides as accidental or undetermined on aggregate level has shown to differ by gender and age and also at the country level [17]. Underreporting may contribute differently to different suicide methods as it has been found to be associated with the coroners' suicide verdict with hanging being most likely to receive suicide verdict [18]. A study focussing on medical practitioners in USA showed that 79 % had specific factors they considered in determining accident over suicide as a cause of death in children, most commonly considered where there was no evidence of suicidal behaviour/intent, and a history of playing choking games and age (the minimum age of considering suicide verdict varied from 2 to 12 years) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Possible underreporting of suicides as accidental or undetermined on aggregate level has shown to differ by gender and age and also at the country level [17]. Underreporting may contribute differently to different suicide methods as it has been found to be associated with the coroners' suicide verdict with hanging being most likely to receive suicide verdict [18]. A study focussing on medical practitioners in USA showed that 79 % had specific factors they considered in determining accident over suicide as a cause of death in children, most commonly considered where there was no evidence of suicidal behaviour/intent, and a history of playing choking games and age (the minimum age of considering suicide verdict varied from 2 to 12 years) [19].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that included open verdicts were regarded as being of higher quality because of evidence that open-verdict cases are often regarded as suicides by researchers. 14,15…”
Section: Strength Of Reporting Scalementioning
confidence: 99%
“…Further, as suicide rates in most countries are elevated among men (in some regions the rate is four times higher among men than women), the lower number of events for women may mean that some studies were underpowered to detect urban-rural variations in female suicide rates. Lower suicide rates in women, overall, may also be attributable to the fact that women are more likely to receive an open verdict than suicide on their death certificate, 228,229 highlighting the need for careful definition of the outcome measure used in an epidemiological enquiry into variation in suicide rates.…”
Section: General Registermentioning
confidence: 99%